НОВЫЕ МАТЕРИАЛЫ К ИСТОРИИ ОТРАРСКОГО ОАЗИСА ДОАРАБСКОЙ ЭПОХИ - Авизова, А.К. (SCIENCE and SOCIETY, 2016)
The article is devoted to preliminary results of archeological excavations of sites of ancient settlement Shakshitobe and Besinshitobe carried out in 2015. At the top of the hill Shakshitobe the rests of a monumental construction till the Arabian epoch have been revealed. Three building periods till the Arabian epoch have been studied. The earliest of designs is the monumental six-meter wall. To the following period the facility №1 belongs. The top brick bookmark relates to the third building period. On Besinshitobe the rests of a large monumental construction have been opened. Thickness of a pise-walled wall of a construction is 7,5 m, the height is 2,5 m. The top building horizon of the epoch of Karakhanis time was not kept.
Keywords: archaeology; culture; oasis; monument; pyramid; epoch